Community-based nutrition education and counselling provided during pregnancy: effects on knowledge and attitude towards iron-folic acid supplementation - Mensur Reshid; Anchamo Anato (Journal of Nutritional Science, 2024)
Maternal malnutrition is pervasive throughout the world, notably in sub-Saharan Africa, including Ethiopia. This study examined the effect of community-based iron-folic acid supplementation (IFAS) nutrition education on IFAS knowledge and attitude among pregnant women in urban settings in South Ethiopia. A community-based quasi-experimental study was conducted among 198 randomly selected pregnant women attending antenatal care (ANC) (99 intervention and 99 control). We used a multistage sampling technique followed by systematic sampling to select the pregnant women. Pregnant women who participated in the intervention arm received six nutrition education sessions and counselling using a health belief model (HBM), while the control group received only routine ANC services. Baseline and endline data were collected during the ANC and compared. The data was analysed using statistical package for social sciences. Analyses of the effect of the intervention were done using difference-in-difference and generalised estimation equation to allow correlation of repeated observations over time. The results indicated a significant effect of intervention on maternal knowledge towards IFAS; with intervention, group levels increased by 35 percentage points (P < 0.001). The odds of being knowledgeable at the endpoint in the intervention group were 2.6 times higher than baseline (OR = 2.67, 95% CI 1.88–3.80). There was a significant (P = 0.001) change in proportion with a favourable attitude towards IFAS between the two time points. The community-based nutrition education intervention approach has significantly improved maternal knowledge and a favourable attitude towards IFAS among pregnant women. The HBM is effective in improving knowledge and attitude among pregnant women.